Aging-associated DNA methylation of LEF1 modulates inflammation and neurodegenerative pathways - Chen, Mengke; Zhou, Lujie; Gao, Yidan; Zhong, Yao; Chen, Cheng; Wang, Zhicheng; Wang, Xiaoning; Xia, Rong (Frontiers in Immunology, 2025)
BackgroundAging is accompanied by profound changes in immune regulation and epigenetic landscapes, yet the molecular drivers underlying these alterations are not fully understood.MethodsTranscriptional profiles of peripheral blood samples from young and elderly individuals, together with aging-associated methylation probe data, were used to identify aging biomarkers. Transcriptomics and chromatin immunoprecipitation sequencing (ChIP-Seq) were conducted to explore potential regulatory mechanisms. Functional validation was performed via knockdown in immune and microglial cell lines, assessing inflammatory responses and reactive oxygen species (ROS) levels. Finally, an independent cohort was recruited to validate expression and promoter methylation, with ChIP-seq and the assay for transposase-accessible chromatin with sequencing (ATAC-seq) analyses supporting epigenetic repression as the underlying mechanism.ResultsLEF1 expression was significantly downregulated in elderly individuals, accompanied by increased promoter methylation, indicating age-related epigenetic repression. Integrated multi-omics analysis linked LEF1 to immune inflammation and neurodegenerative pathways. LEF1 knockdown enhanced inflammatory responses and ROS production in vitro. ChIP-seq and ATAC-seq data supported epigenetic repression as a mechanism for age-related LEF1 silencing.ConclusionsAge-related epigenetic repression of LEF1 contributes to immune-inflammatory activation and may underlie neurodegenerative processes.